2017
DOI: 10.1111/sena.12237
|View full text |Cite
|
Sign up to set email alerts
|

Does Participation in National Commemorations Increase National Attachment? A Study of Dutch Liberation Festivals

Abstract: It is generally assumed that national commemorations have the power to increase national attachment. This is because such ceremonies highlight shared history, communicate core values, and have the potential to decrease conflicts in societies, while celebrating and mourning together enhances attachment to the group. Remarkably, only a limited number of studies have empirically studied the relation between participation in national commemorations and feelings of national attachment. Studies that have addressed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…This creates pride, honor, respect, visibility, and identity for these people who see their ethnic communities and cultural traditions being noticed by mainstream society. This result is in line with some of the earlier research (e.g., [30][31][32]34]). Some illustrative quotations are:…”
Section: Integration and Communitysupporting
confidence: 93%
See 1 more Smart Citation
“…This creates pride, honor, respect, visibility, and identity for these people who see their ethnic communities and cultural traditions being noticed by mainstream society. This result is in line with some of the earlier research (e.g., [30][31][32]34]). Some illustrative quotations are:…”
Section: Integration and Communitysupporting
confidence: 93%
“…Positive emotions and feelings at festivals can also be expressed in different dimensions and by using many everyday terms, such as joy, pleasure, happiness, etcetera [29]. Other authors (e.g., [30]) include feelings such as attachment, belonging, unity, and solidarity. One more aspect is the sense of pride as a source of identity-feeling for festival participants [31,32], who in some cases might belong to discriminated groups in the community [33].…”
Section: Positive Feelings: Definition and Criteriamentioning
confidence: 99%
“…The case study research is appropriate for identifying, describing, analyzing and also theorizing of this social event [27]. The 'invented tradition' and 'collective memory' issues are discussed through the case study research method in many studies connected with the issues including 'nationality', 'locality', 'identity' and 'tradition' [18][19][20][21][22][23]. Among these studies, few are constructed on the relation between the concepts of 'invented tradition', 'collective memory' and 'festival' [20][21][22].…”
Section: Methodsmentioning
confidence: 99%
“…Stankova and Vassenska draw attention to festivals' and local events' contribution to the conservation of cultural heritage and traditions [18]. Kong and Yeoh, Regt and Lippe; Parvez; Repšienė and Žukauskienė; and, Crespi-Vallbona and Richards analyze specific cases to reveal how officially produced events were instrumental to building up nations and national identity [19][20][21][22][23].…”
Section: Introduction and Theoretical Backgroundmentioning
confidence: 99%
“…This research design enabled the researchers to compare those who participated in the ceremonies and those who did not. The authors found that participation in the national ceremony was not related to national identity (see also, de Regt & Lippe, ). Another attempt to evaluate the impact of national days was conducted in Israel.…”
Section: National Days National Identity and Collective Memorymentioning
confidence: 99%